The importance of halal processing assistant for Indonesian SMEs / Muhammad Ikbal, Femilia Zahra and Suryadi Hadi - Ikbal, Muhammad; Zahra, Femilia; Hadi, Suryadi (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This article provides an overview of the Halal industry in Indonesia and the challenges faced by small and medium-sized enterprises (SMEs) in obtaining Halal certification. It then explores the importance of Halal Processing Assistants in supporting SMEs in the certification process, including their role in identifying and eliminating non-Halal ingredients and processes, accessing new markets, and improving the quality and safety of products. The article also discusses potential disadvantages of using Halal Processing Assistants, such as cost and dependence on third-party support, as well as the relationship between Halal Processing Assistants and institutional pressures. Finally, the article highlights areas for future research, including the development of new Halal technologies and the impact of Halal Processing Assistants on SME growth and sustainability